Morphological variations of mangosteen fruits from Luzon and Mindanao Islands, the Philippines - Julie Berame; N. LAWSIN; F. MIGUEL; J. CHAVEZ (Society for Indonesian Biodiversity, 2020)
Abstract. Berame J, Lawsin N, Miguel F, Chavez J. 2020. Morphological variations of mangosteen fruits from Luzon and Mindanao Islands, the Philippines. Biodiversitas 21: 3094-3100. Luzon and Mindanao islands in the Philippines are the important mangosteen producing provinces whose growing areas are scattered on these two islands. With this, mangosteen variability was detected based on field fruit collections in summer of 2019. The morphological variations of mangosteen fruits were observed and collected in Quezon Province in Luzon and Davao-Zamboanga Provinces in Mindanao based on the total number of 175 mangosteen trees. The main objectives of the research were to find out the morphological variations of mangosteen fruits and using Tomato Analyzer 4.0 to determine the morphological characters that can be used to differentiate mangosteen accessions in the Philippines. The variables include fruit shape index (external and internal), curve fruit shape index, asymmetry, internal eccentricity and weight of the ripe fruits. The results show that fruit characters like ellipsoidal, circular, rectangular, lobe shape, size, pericarp area, and pericarp thickness. are highly resemblance particularly in its fruit shape characters, and even sharing a similar taste of ripe fruits. Data revealed that Garcinia mangostana shared a similar character with Garcinia malaccensis even though they are from different geographical areas. Based on the morphological variations and characters, the two varieties of mangosteen fruits in the Philippines, G. mangostana and G. malaccensis, are so closely related that they could be combined together as one species as identified in the morphological analysis of this study.